PENERAPAN SISTEM PENGELOLAAN SURAT MASUK DAN SURAT KELUAR BAGIAN ORGANISASI SEKRETARIAT DAERAH KOTA MEDAN - Meha, Nurmala Luthfi; Nasution, Annio Indah Lestari (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
The purpose of the incoming and outgoing mail management system in the Organization Section of the Medan City Regional Secretariat is to improve the management of correspondence documents, both digitally and manually. This system records and processes each letter in a structured manner, making it easier to archive and track later. Data were collected through direct observation and interviews in this descriptive qualitative study. The results of the study indicate an urgent need to switch to a digital mail management system, although this system is still done manually at this time. This will improve productivity, accountability, and information security. In an organization, there are two types of letters: incoming and outgoing mail. Incoming mail is a file given by an organization to another party. Outgoing mail, on the other hand, is a document created by an organization to be sent to another party. The management stages include 1) Receiving Incoming Mail, 2) Sorting Letters, 3) Recording Letters, 4) Delivering Letters, 5) Duplicating Letters, and 6) Storing archives. First, creating an idea for a letter; second, checking and signing it; third, recording the identity of the letter; fourth, sending it; and fifth, keeping records. It is hoped that the implementation of a better system will facilitate communication and coordination between parties in government.